The Effect of Local Area Crime on Mental Health - Christian Dustmann; Francesco Fasani (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
This paper analyses the effect of local crime rates on residents' mental health. Using longitudinal information on individuals' mental well-being, we address the problem of sorting and endogenous moving behaviour. We find that crime causes considerable mental distress for residents, mainly driven by property crime. Effects are stronger for females, and mainly related to depression and anxiety. The distress caused by one standard deviation increase in local crime is 2-4 times larger than that caused by a one standard deviation decrease in local employment, and about one seventh of the short-term impact of the 7 July 2005 London Bombings.
Keywords: I18; K42; R23; 330; neighbourhoodeffects; mentalwellbeing; fearofcrime